1993
DOI: 10.1002/aja.1001960109
|View full text |Cite
|
Sign up to set email alerts
|

Fibrillin delineates the primary axis of the early avian embryo

Abstract: Chicken embryos were immunolabeled with antibodies to fibrillin, an extracellular matrix molecule implicated in the Marfan syndrome. The pattern of labeling, established using both whole-mounted and sectioned embryos, showed a striking localization at the primary axis of the early embryo, including Hensen's node. After stage 8, the labeling of Hensen's node diminished while other structures in the embryo exhibited increased immunolabeling. These structures include the region of the presumptive dorsal aorta, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 40 publications
(34 reference statements)
3
28
0
Order By: Relevance
“…It was recently shown that elastin is expressed much earlier than previously thought (Visconti et al, 2003), but it is still far behind the initial expression of fibrillin-1 and -2 (Gallagher et al, 1993;Wunsch et al, 1994) and FB1 antigen (Fig. 2).…”
Section: Discussionmentioning
confidence: 82%
“…It was recently shown that elastin is expressed much earlier than previously thought (Visconti et al, 2003), but it is still far behind the initial expression of fibrillin-1 and -2 (Gallagher et al, 1993;Wunsch et al, 1994) and FB1 antigen (Fig. 2).…”
Section: Discussionmentioning
confidence: 82%
“…Every vertebrate embryo that has been examined exhibits peri-notochordal fibrillin immunoreactivity (Gallagher et al, 1993;Rongish et al, 1998;Quondamatteo et al, 2002;Visconti et al, 2003). Highresolution localization studies of Fbn 2 during avian development using the same antibody (JB3) as employed in this study reveal a difference in the timing of appearance of Fib 2 in the notochord-somite boundary between avian and amphibian embryos.…”
Section: The Notochord-somite Boundarymentioning
confidence: 77%
“…Fbn 3 is also present in embryos, but its distribution is less well characterized (Corson et al, 2004). In the chicken dorsal axis, a mechanical role for the fibrillins in maintaining tissue integrity has been postulated, both prior to notochord development and at later stages as a fibrillar, basket-like network holding axial embryonic elements such as notochord, somites, dorsal aorta, and gut in relative position (Gallagher et al, 1993;Wunsch et al, 1994;Rongish et al, 1998;Czirok et al, 2004). The dynamic behavior of Fbn 2 fibrils during axis formation in the chicken embryo reveals strong cell-matrix interactions, because fibril displacement in the axis is similar to the pattern of cell movement described in the gastrula (Czirok et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…It has been clearly established that all animal species have specific extracellular matrix components which provide their tissues with the tensile properties which are required to meet the demands of mechanical stress (Sage and Gray, 1979). Gallagher et al, (1993) have previously suggested a mechanical function for fibrillin in the process of gastrulation. The heart, even during the earliest stages of development, undergoes significant mechanical stress (Clark and Hu, 1982) and therefore most probably requires a specialized elastic matrix.…”
Section: First Periodmentioning
confidence: 99%